Natural gas industry transformation in Peninsular Malaysia: The journey towards a liberalised market - Lim, Zhen Wen; Goh, Kim Leng (Elsevier, 2019)
Malaysia's gas industry has been undergoing a profound transformation that is imperative in ensuring energy security. The rising demand especially in Peninsular Malaysia and regulating prices of natural gas saw PETRONAS selling natural gas at a relatively low price that affects the Government's revenue collection negatively. This article contextualised the changes in the law and policy that concerns the management of gas resources in Malaysia. The journey from a price regulated gas market towards a liberalised market is explained. This energy transition process requires more than changes in the law. It involves the synergy of dynamics from various aspects to ensure that the ecosystem is conducive for the development of a healthy natural gas sector to ensure secured energy supply, while catalysing the growth of new industries and generating new revenues for the nation. The challenges and pushbacks throughout this journey are highlighted. Discussions show how the problems were tackled strategically within the political, social and economic domains, as well as the interaction between them. These interactions demonstrate the importance of energy justice in policy making. Policy decisions are made to balance the competing goals of various key stakeholders.